Thermographic assessment of skin prick tests in comparison with the routine evaluation methods - Rok, Tomasz; Rokita, Eugeniusz; Tatoń, Grzegorz; Guzik, Tomasz; Śliwa, Tomasz (Advances in Dermatology and Allergology/Postępy Dermatologii i Alergologii, 2016)
Introduction :Theskin prick test is still the first and basic procedure in the diagnosis of allergic diseases. The possibility of using a sensitive thermographic method supported by the mathematical model for the assessment of skin test results will be highlighted in the studies. Aim :To compare the proposed approach with routine planimetric and thermographic methods. Material and methods: A mathematical model of allergic reaction was developedSimplifying assumptions of the IgE-mediated skin reaction is the essence of the model. Investigations were performed in a group of 40 patients. Results: Using the spatio-temporal evolution of temperature distributions, the ratios of the histamine released from mast cells to the control histamine were determined. The obtained values very well correlate with the standard evaluation of skin prick tests (correlation coefficient = 0.98). Conclusions : The proposed method of skin test evaluation presents several advantages. The continuous acquisition of data provides the monitoring of time course of the allergic response. The transport of mediator and its concentration were distinctly discriminated, which may be diagnostically useful, especially for abnormal cases. The high sensitivity of the method enables studying patients regardless of age and skin sensitivity.